Gambaran Tingkat Stres dan Kejadian Hyperemesis Gravidarum Pada Ibu Hamil - Pane, Mustika; Tarigan, Abul A’la; Tiara, Anita (Sagita Academia Journal, 2024)
Hyperemesis Gravidarum is an incidence of nausea and vomiting in pregnant women that occurs excessively so that it interferes with activities. Many factors cause this condition, one of which is psychological. Psychological factors in the form of stress are considered to play an important role as a cause of hyperemesis gravidarum. This study aims to his study aims to identify stress levels and the incidence of hyperemesis gravidarum in pregnant women. The research method is descriptive quantitative with a cross-sectional approach. The study population was all pregnant women who checked their pregnancy as many as 249 respondents. The research sample used accidental sampling technique and obtained as many as 153 respondents. The results of the study showed that the stress level in pregnant women was in the moderate category for 107 people (69.9%), and the incidence of hyperemesis gravidarum was in the moderate category for 95 people (62.1%). Based on the results of this study, counseling is needed for pregnant women to be able to adapt and prepare for their pregnancy.